2009
DOI: 10.2527/jas.2009-2041
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genetic relationships of residual feed intake with performance and ultrasound carcass traits in Brangus heifers1

Abstract: The objective of this study was to characterize residual feed intake (RFI) and to estimate phenotypic and genetic correlations with performance and ultrasound carcass traits in growing heifers. Four postweaning feed efficiency trials were conducted using 468 Brangus heifers. The complete Brangus pedigree file from Camp Cooley Ranch (Franklin, TX), which included 31,215 animals, was used to generate genetic parameter estimates. The heifer progeny from 223 dams were sired by 36 bulls, whereas the complete pedigr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
56
5
10

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(95 citation statements)
references
References 28 publications
24
56
5
10
Order By: Relevance
“…The base RFI regression model (DMI explained by MLW and ADG) in this study accounted for 0.66 of the variation in DMI, which is comparable to other studies (Lancaster et al, 2008 and2009a;Shaffer et al, 2011) where high forage diets were fed (R 2 range from 0.53 to 0.64). These values are lower than those (0.71 to 0.77) obtained when RFI is determined on cattle fed high-energy diets (Basarab et al, 2003;Lancaster et al, 2009b;Kelly et al, 2010a).…”
Section: Discussionsupporting
confidence: 70%
“…The base RFI regression model (DMI explained by MLW and ADG) in this study accounted for 0.66 of the variation in DMI, which is comparable to other studies (Lancaster et al, 2008 and2009a;Shaffer et al, 2011) where high forage diets were fed (R 2 range from 0.53 to 0.64). These values are lower than those (0.71 to 0.77) obtained when RFI is determined on cattle fed high-energy diets (Basarab et al, 2003;Lancaster et al, 2009b;Kelly et al, 2010a).…”
Section: Discussionsupporting
confidence: 70%
“…A lower coefficient of determination (R 2 = 0.54) was obtained for the estimation of RFI met when the same diet was offered, explaining 54% of the variation in DMI. This value was higher than the 43% observed by Lancaster et al (2009) for heifers fed alfalfabased diet and concentrate, and the 38% observed by Freetly and Brown-Brandl (2013) for heifers fed a high-roughage diet. The short duration (32 d) of ADG measurement may have compromised the calculation of RFI met .…”
Section: Resultscontrasting
confidence: 43%
“…O coeficiente de correlação entre CAR e CA foi significativo (r = 0,63, P<0,01) e maior que os descritos por Arthur et al (2001a), Lancaster et al (2009) e Kelly et al (2010 para bovinos em crescimento de 0,53, 0,59 e 0,46, respectivamente, porém inferior ao estimado para cordeiros (r CAR = 0,73) por Knott et al (2010). Seria importante verificar a existência de correlação genética de mesmo sentido entre tais parâmetros para ovinos, assim como encontrado em bovinos (Lancaster et al, 2009), pois, dessa forma, uma seleção para CAR melhoraria também a conversão alimentar dos animais.…”
Section: Methodsunclassified
“…Seria importante verificar a existência de correlação genética de mesmo sentido entre tais parâmetros para ovinos, assim como encontrado em bovinos (Lancaster et al, 2009), pois, dessa forma, uma seleção para CAR melhoraria também a conversão alimentar dos animais. Apesar da correlação moderada entre CAR e CA no presente estudo, não houve diferença entre as classes de eficiência para este último componente.…”
Section: Methodsunclassified